The Relationship of Mother's Role in Stimulation with Motor Development in Toddler - B, Suriani; Nurfatimah, Nurfatimah; Saadong, Djuhadiah; Subriah, Subriah; Ramadhan, Kadar (JURNAL INFO KESEHATAN, 2022)
Toddler period is an important phase in the growth and development of children. The role of parents, especially mothers, is needed to help children develop motor skills so that children's development can be maximized. The objective of this study is to analyze the mother's role in stimulating the child's motor development. The research method is cross sectional. The population in this study were mothers who had children aged 1-3 years in the work area of the Mangasa Primary Health Center, Makassar, amounting to 45 people. The sample in this study was 45 people, taken with a saturated sampling technique or the total population. The statistical test used the chi square test. The results presented that 95.7% of mothers who played a role in stimulating children's motor development had children whose development was appropriate. The results of the chi square test obtained p value <0.001. The conclusion is that there is a relationship between mother's role in stimulation and the motor development of toddler. It is expected that the Primary Health Center or midwives will provide training to mothers about providing developmental stimulation so that mothers can independently assess their child's development and pay attention to their child's development according to age.